The Experimental Tobacco Marketplace: Narratives engage cognitive biases to increase electronic cigarette substitution. (1st April 2019) - DeHart, William Brady; Mellis, Alexandra M.; Kaplan, Brent A.; Pope, Derek A.; Bickel, Warren K.
Highlights: Substituting e-cigarettes for cigarettes may minimize health losses. Public health narratives are one effective strategy for encouraging substitution. The Experimental Tobacco Marketplace (ETM) is a tool to study narrative effectiveness. Narratives decreased cigarette, and increased e-cigarette purchasing in the ETM. Narratives are a promising intervention in the ETM with translational potential. Abstract: Background: The Experimental Tobacco Marketplace (ETM) is a digital storefront in which participants can purchase tobacco products using an account balance that reflects their typical tobacco product purchasing. The ETM is also an ideal resource to investigate the harm-reduction potential of alternative nicotine products such as e-cigarettes. In a series of experiments, we explored the effects of harm-reduction narratives that encouraged e-cigarette substitution of conventional cigarettes in the ETM. These narratives incorporated different cognitive biases in order to determine which strategy is most effective. Methods: In both experiments, participants, recruited from Amazon Mechanical Turk, read a narrative about a friend that either falls ill or faces financial difficulties and then made purchases in the ETM. Some of these narratives specifically incorporated different cognitive biases including trusting authority. Across ETM trials, the price of conventional cigarettes increased while the price of the alternative products, including e-cigarettes, remained constant. Results: Across both experiments, a general pattern emerged supporting the effectiveness of narratives in increasing e-cigarette purchasing. Importantly, from a harm-reduction perspective, this increase in e-cigarette substitution frequently corresponded with a decrease in conventional cigarette purchasing. Conclusions: Narratives can decrease conventional cigarette and increase e-cigarette purchasing in an ETM that mimics real-world marketplaces. Invoking different cognitive biases may bolster this effect. Narratives can be a valuable harm-reduction tool because they are cost-effective, can be widely disseminated, and can be personalized to individuals.